2022
DOI: 10.3389/fendo.2022.989815
|View full text |Cite
|
Sign up to set email alerts
|

Human stem cell derived beta-like cells engineered to present PD-L1 improve transplant survival in NOD mice carrying human HLA class I

Abstract: There is a critical need for therapeutic approaches that combine renewable sources of replacement beta cells with localized immunomodulation to counter recurrence of autoimmunity in type 1 diabetes (T1D). However, there are few examples of animal models to study such approaches that incorporate spontaneous autoimmunity directed against human beta cells rather than allogenic rejection. Here, we address this critical limitation by demonstrating rejection and survival of transplanted human stem cell-derived beta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 74 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Harnessing these approaches, various investigators have sought to generate hypoimmunogenic stem cell lines that could suppress the ability for cells to be detected by the immune system (Figure 2). Several groups have reported that HLA class I molecules are upregulated on the surface of beta cells in T1D organ donors and upon exposure to T1D mimicking, proinflammatory culture conditions [66][67][68]. HLA class I molecules are an integral piece of the process to activate cytotoxic CD8 + T cells through their engagement with the CD8 T cell receptor.…”
Section: Generating Immune-privileged Beta Cellsmentioning
confidence: 99%
“…Harnessing these approaches, various investigators have sought to generate hypoimmunogenic stem cell lines that could suppress the ability for cells to be detected by the immune system (Figure 2). Several groups have reported that HLA class I molecules are upregulated on the surface of beta cells in T1D organ donors and upon exposure to T1D mimicking, proinflammatory culture conditions [66][67][68]. HLA class I molecules are an integral piece of the process to activate cytotoxic CD8 + T cells through their engagement with the CD8 T cell receptor.…”
Section: Generating Immune-privileged Beta Cellsmentioning
confidence: 99%